1989
DOI: 10.1161/01.cir.79.3.580
|View full text |Cite
|
Sign up to set email alerts
|

Hypertrophic cardiomyopathy in the elderly. Distinctions from the young based on cardiac shape.

Abstract: The striking clinical and pathologic features of hypertrophic cardiomyopathy have been defined almost exclusively in the young. Little is known about this condition in the elderly, although it is assumed to be part of a single disease. Accordingly, we studied 28 patients who were 65 years of age and older (mean age, 72±6.4 years) who were diagnosed as having hypertrophic cardiomyopathy by M-mode, two-dimensional, and Doppler echocardiography and compared them with a group of 28 consecutive patients with this d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
73
0
2

Year Published

1990
1990
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 166 publications
(79 citation statements)
references
References 26 publications
4
73
0
2
Order By: Relevance
“…14,15 Our study results of significantly more SAM in male than female patients (78.3 vs 47.4%, p=0.0008) can be accounted for, at least in part, by the age differential between the present male and female patients. After adjustment for age, we found that the difference in the prevalence of SAM became marginally significant (p=0.0670).…”
Section: Systolic Anterior Movement Of the Mitral Valve (Sam)mentioning
confidence: 49%
See 2 more Smart Citations
“…14,15 Our study results of significantly more SAM in male than female patients (78.3 vs 47.4%, p=0.0008) can be accounted for, at least in part, by the age differential between the present male and female patients. After adjustment for age, we found that the difference in the prevalence of SAM became marginally significant (p=0.0670).…”
Section: Systolic Anterior Movement Of the Mitral Valve (Sam)mentioning
confidence: 49%
“…13 Our results are also consistent with other published studies, which demonstrated statistically significant thicker IVS and LVPW in youthful patients with HCM than in the elderly. 14,15 In fact, after adjustment for age, we found that the difference in IVSt became statistically insignificant (p=0.1948).…”
Section: Interventricular Septal Wall Thicknessmentioning
confidence: 75%
See 1 more Smart Citation
“…5,[12][13][14] They reportedly show more predominantly an ovoid LV cavity contour with normal septal curvature, a proximal septal bulge, and mitral 12 In addition, the prevalence of a proximal septal bulge and mitral annular calcification was higher in the elderly patients than that in the young patients. Lewis et al reported that obstruction in the small LVOT was frequent in the elderly, in addition to an ovoid-shaped LV cavity.…”
Section: Morphologic Characteristics Of Hcm In the Elderlymentioning
confidence: 99%
“…Wigle score was also calculated as previously reported. 19 Furthermore, we studied the morphologic features according to the report by Lever et al 12 In brief, (1) septal curvature was evaluated in the apical 4-chamber view (Fig 1). An abnormal convexity of the septum toward the LV cavity was defined as reversed septal curvature, which produced a crescent-shaped LV cavity.…”
Section: Subjectsmentioning
confidence: 99%